Drug interaction between bortezomib and tuberculosis treatment: a case report. Issue 3 (30th September 2013) - Cuny, Pascale; Marfaing-Koka, Anne; Lottmann, Marion; Rieutord, André; Barbault-Foucher, Severine
Abstract : An adult patient was diagnosed with plasmacytoma and monoclonal gammopathy. An increase in IgG λ and myeloma stage IIIa without cytogenetic abnormalities was found. The patient was treated with dexamethasone, bortezomib and pegylated liposomal doxorubicin. A decrease in monoclonal protein was observed during the first four cycles of chemotherapy. Isoniazid and rifampicin were introduced following suspected tuberculosis. Then, an increase in monoclonal gammopathy led to the combination of lenalidomide and chemotherapy. The persistent increase in the monoclonal component suggested a possible interaction between rifampicin and bortezomib. Tuberculosis treatment was stopped and a decrease in monoclonal protein during subsequent courses and regression of lesions on CT scan images confirmed this interaction to be likely. To our knowledge, this is the first report of concomitant administration of bortezomib with rifampicin. Therefore, a potential interaction between bortezomib and rifampicin should be anticipated during concomitant administration in the future.